The effect of career development and placement on job satisfaction which impacts the company's employee performance - Karneli, Okta; Nurpeni, Nurpeni; Astuti, Widia; Ruzikna, Ruzikna (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The company is one of the important sectors in improving the country's economy, and every company certainly wants optimal income. Therefore, human resources are an important aspect to continue improving as one of the driving forces so that the company runs optimally through work placements tailored to their abilities. This underlies the researcher to obtain further information about the effect of career development and placement on job satisfaction which impacts the performance of company employees. This study aimed to determine whether Career Development and Placement Affect Job Satisfaction Impacts Company Employee Performance. The research method used is descriptive quantitative with data collection techniques through observation and questionnaires to 50 respondents at XYZ company. The results showed that career development and placement affected job satisfaction, with an influence value of 21.2%. Job satisfaction positively and significantly affected employee performance, with an influence value of 81.7%. So career development is a long process that every company must provide as an obligation to provide opportunities for employees to pursue career development.